Change in β2-agonist use after severe life events in adults with asthma: A population-based cohort study Life events and bronchodilator usage among adults with asthma - Lietzen R; Virtanen P; Kivimaki M; Korkeila J; Suominen S; Sillanmaki L; Koskenvuo M; Vahtera J (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Objective: This prospective, population-based cohort study of 1102 Finnish adults with asthma, examined whether exposure to stressful life events is associated with the intensity of usage of inhaled short-acting beta(2)-agonists.Methods: Survey data was collected by two postal questionnaires. Baseline characteristics were obtained in 1998 and data on 19 specific stressful events (e.g. death of a child or spouse or divorce) within the six preceding months in 2003. Exposure to life events was indicated by a sum score weighted by mean severity of the events. Participants were linked to records of filled prescriptions for inhaled short-acting beta(2)-agonists from national registers from 2000 through 2006. The rates of purchases of short-acting beta(2)-agonists before (2000 2001), during (2002 2003) and after (2004-2006) the event exposure were estimated using repeated-measures Poisson regression analyses with the generalized estimating equation.Results: Of the 1102 participants, 162 (15%) were exposed to highly stressful events, 205 (19%) to less stressful events. During the 7-year observation period, 5955 purchases of filled prescription for inhaled short-acting beta(2)-agonists were recorded. After exposure to highly stressful events, the rate of purchases of beta(2)-agonists was 1.50 times higher (95% confidence interval (CI): 1.05, 2.13) than before the stressful event occurred. Among those with low or no exposure to life events, the corresponding rate ratios were not elevated (rate ratio 0.81, 95% CI: 0.66, 0.99 and 0.95, 95% CI: 0.83, 1.09 respectively).Conclusion: An increase in beta(2)-agonist usage after severe life events suggests that stressful experiences may worsen asthma symptoms.